2018
DOI: 10.14341/osteo20173108-113
|View full text |Cite
|
Sign up to set email alerts
|

Role of parathyroid hormone measurement in fine-needle aspiration biopsy washout in diagnosis and treatment of primary hyperparathyroidism

Abstract: Остеопороз и остеопатии / Osteoporosis and Bone Diseases | 108 CASE REPORT АКТУАЛЬНОСТЬПервичный гиперпаратиреоз (ПГПТ) -первичная, т. е. не спровоцированная пониженным уровнем каль-ция в крови, гиперпродукция паратгормона (ПТГ), кото-рая приводит к нарушению гомеостаза кальция.Заболеваемость ПГПТ составляет около 20 случаев на 100 тыс. населения в год; в течение последних лет на-блюдается ее неуклонный рост в связи с повышением и информативности и доступности методов диагностики ПГПТ. Распространенность ПГПТ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, in certain circumstances, the need to further identify the culprit gland, including measurement of high PTH in a lesion suspected as a parathyroid adenoma, becomes relevant. These circumstances include discordant imaging findings, 3–5 challenging anatomy (multinodular goiter or concomitant Hashimoto's thyroiditis), 6–8 intrathyroid adenoma, 9 and a history of neck surgery 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in certain circumstances, the need to further identify the culprit gland, including measurement of high PTH in a lesion suspected as a parathyroid adenoma, becomes relevant. These circumstances include discordant imaging findings, 3–5 challenging anatomy (multinodular goiter or concomitant Hashimoto's thyroiditis), 6–8 intrathyroid adenoma, 9 and a history of neck surgery 5 …”
Section: Introductionmentioning
confidence: 99%
“…These circumstances include discordant imaging findings, [3][4][5] challenging anatomy (multinodular goiter or concomitant Hashimoto's thyroiditis), [6][7][8] intrathyroid adenoma, 9 and a history of neck surgery. 5 A number of studies showed excellent sensitivity (up to 95%) and positive predictive value (PPV, up to 100%) of PTH washout [10][11][12][13][14][15] ; and provided reassurance regarding the immediate safety of the procedure.…”
mentioning
confidence: 99%